Detecção de falhas de estator em motores de indução trifásicos utilizando transformada wavelet, medida RMS e potência de previsão - Vitor, Avyner Lorran de Oliveira (2015)
The Three-Phase Induction Motor is the most utilized electrical machine in industrial envi- ronments. It is an equipment that shows robust construction, ease maintenance, low cost and reliability. However, frequently, machines are exposed to thermal, electrical and mecha- nical efforts, which, over time, result in a failure. This work aims to analize the stator short circuit fault, one of the most frequent induction motor failures. Therefor, the peculiarities of the signals that are reflected in stator current are investigated, in order to correlate the signal characteristics to the failure in question. Current signals are processed through the Fourier and Wavelet transform in order to analyse short-circuit specific frequencies. Subse- quently, the classification is performed through two artificial neural networks, the multilayer perceptron and the Radial Basis Function.